THE TENDENCY OF THE INTERNATIONAL TRADE OF ROMANIA AND CHINA - A COMPARATIVE ANALYSIS - Cecilia-Irina, Rabontu; Ana-Gabriela, Babucea (European Scientific Journal, ESJ, 2014)
Today, China’s economy is the second largest in the world, after the U.S. and followed closely by Japan’s economy on the 3rd place, beeing a model for other countries, given that it overcame the crisis without major shocks and even recorded more new achievements.After the revolution of 1989, the Romanian economy leaving the Communist leadership, a system that exists in China, has gone through dramatic changes that have generated a total reconfiguration of the foreign trade. At the same time, the economic and political instability have had seriously reverberations on the Romanian economy, manifested by increasing prices, reducing the salaries or the wage gains, reducing number of jobs and so increasing the unemployment rate, the growth rates of credit due to devaluation of the national currency, increasing the value added tax, reducing consumption, etc.Between China and Romania there are bilateral economic relations, China representing the fifth partner of Romania in import tranzactions, so, in this paper we will try to conduct an analysis of the economic situation of Romania versus China’s economy, economy which has stunned the whole world. The aims of this paper is to identify the similarities and differences in terms of the tendency of evolution of the main indicators characterizing the two countries’ economies, the fact that Romania has changed the partners on the international markets lately, also identifying the main categories of products and services for which Romania and China have entered the export-import relations.